1993
DOI: 10.1136/vr.133.11.260
|View full text |Cite
|
Sign up to set email alerts
|

Feline bordetellosis: challenge and vaccine studies

Abstract: Four eight-week-old cats, shown to be free from feline calicivirus, feline herpesvirus and Chlamydia psittaci were challenged with an aerosol of Bordetella bronchiseptica. Within five days the cats developed signs of respiratory disease, characterised by nasal discharge, sneezing, spontaneous or induced coughing and dry or wet rales at auscultation. These signs were present for about 10 days, after which they began to resolve. To test the protective capacity of an experimental fimbrial antigen-based subunit va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0
4

Year Published

1996
1996
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 0 publications
3
33
0
4
Order By: Relevance
“…and are also important immunologically [14,21]. Indeed, fimbrial components have been included in acellular vaccines against B. pertussis [22] and in a B. bronchiseptica vaccine for cats [9]. Variation between the Fim2 and Fim3 proteins of B. pertussis and B. bronchiseptica has been reported in previous studies [16].…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…and are also important immunologically [14,21]. Indeed, fimbrial components have been included in acellular vaccines against B. pertussis [22] and in a B. bronchiseptica vaccine for cats [9]. Variation between the Fim2 and Fim3 proteins of B. pertussis and B. bronchiseptica has been reported in previous studies [16].…”
Section: Discussionmentioning
confidence: 82%
“…Isolation rates in the cat population ranging from 3% to 11% and seroprevalence rates of between 24% and 79% have been reported, and in epidemiological studies a significant association with respiratory disease has been found in some cat populations [4][5][6][7]. Also, respiratory disease has been reproduced experimentally in specificpathogen-free cats, confirming that this organism can be a primary pathogen in this species [8,9].…”
Section: Introductionmentioning
confidence: 78%
“…Αν και ορολογικές μελέτες έχουν δείξει πως μεγάλος αριθ μός γατών έχει εκτεθεί στη Β. bronchiseptica 3 , ο αιτιολο γικός της ρόλος έχει μελετηθεί περισσότερο κάτω από ερ γαστηριακές και λιγότερο κάτω από φυσικές συνθήκες. Για την πληρέστερη κάλυψη των ζώων και με βάση τα πο λύ καλά αποτελέσματα που είχε η χρήση ενός εμβολίου υ-πομονάδας κατά της Β. bronchiseptica 3 συνιστάται ο εμβο λιασμός παρά τις επιφυλάξεις ως προς την ασφάλεια, και την αποτελεσματικότητα του εμβολίου αυτοΰ 13 .…”
Section: οι εμβολιασμοι στη γατα 1 σύνδρομο της ανώτερης αναπνευστικunclassified
“…Fimbriae important in humoral immune response against B. bronchiseptica (4,18,19) was also included in a vaccine for cats (13). Fimbriae was initially demonstrated to be constituted of three antigenically related 21, 22 and 24 kDa fimbrial major subunit proteins by Lee et al (1986) and shown to be expressed in variant quantities effecting the host species specificity of B. bronchiseptica strains (4).…”
Section: Introductionmentioning
confidence: 99%
“…Fimbriae was initially demonstrated to be constituted of three antigenically related 21, 22 and 24 kDa fimbrial major subunit proteins by Lee et al (1986) and shown to be expressed in variant quantities effecting the host species specificity of B. bronchiseptica strains (4). By different studies, fimbrial subunits of B. bronchiseptica were determined as Fim2, Fim3, FimX (expressed only at very low levels), FimA, FimN and FimD (3,8,13,20,21,26,28). Although being the minor fimbrial subunit, 40 kDa FimD, have important role in adhesion by affecting the expression of the major fimbrial subunits and being necessary in formation of the fimbrial structure (8,31).…”
Section: Introductionmentioning
confidence: 99%